Enhancing Decolorization for Methyl Orange in Aqueous Solution by Graphene Supported Nanoscale Zero Valent Iron - Zhang, Feng-Jun; Xuan, Han; Xie, Fa-Zhi; Jiang, Tao; Chen, Tao; Oh, Won-Chun (Asian Journal of Chemistry, 2012)
Nanoscale zero valent iron-graphene has been synthesized via a simple effective chemical method. The composite nanosheets are super paramagnetic at room temperature and can be separated by an external magnetic field. The prepared nanoscale zero valent iron-graphene nanosheets were characterized by X-ray diffraction, transmission electron microscopy. The results demonstrated the successful attachment of nanoscale zero valent iron nanoparticles to graphene nanosheets. It was found that the nanoscale zero valent iron-graphene nanosheets not only show near complete methyl orange decolorization within 0.5 h under natural lighting, but they are also practically usable for methyl orange separation from water.